Layered porous carbon, preparation method thereof and supercapacitor

By designing a hierarchical porous carbon structure in carbon-based materials and optimizing the pore structure and hybridization type, the problem of using strong alkaline substances in the preparation process of existing carbon-based materials is solved, and the electrochemical performance is improved, achieving environmental protection and cost-effectiveness. Efficient supercapacitor materials.

CN119361331APending Publication Date: 2025-01-24GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411532420.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The introduction of the strong alkaline substance potassium hydroxide during the preparation process of existing carbon-based materials is high in cost and harmful to the environment, and its electrochemical performance needs to be further improved to meet the needs of supercapacitors.

Method used

Design a layered porous carbon material that optimizes the pore structure and hybrid types in the first -porous carbon layer and the second polychide carbon layer, forming an internal high -SP2 hybrid medium and large pore structure, as well as surface height SP3 hybrid microporous structures improve the surface area and conductivity.

Benefits of technology

A carbon -based material with a reasonable pore structure, higher surface area, and excellent conductivity, improved electrochemical performance, and the preparation method of this material is environmentally friendly and cost -effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361331A_ABST
    Figure CN119361331A_ABST
Patent Text Reader

Abstract

The invention relates to layered porous carbon, a preparation method thereof and a supercapacitor. The layered porous carbon comprises a first porous carbon layer and a second porous carbon layer located on the surface of the first porous carbon layer. Carbon atoms in the layered porous carbon comprise sp3 carbon atom hybrid bonds and sp2 carbon atom hybrid bonds, and the pore structure of the layered porous carbon comprises micropores, mesopores and macropores; in the first porous carbon layer, the sp2 carbon atom hybrid bond content is gt; the sp3 carbon atom hybrid bond content and the total volume ratio gt of mesopores and macropores; the volume ratio of the micropores; in the second porous carbon layer, the sp3 carbon atom hybrid bond content is gt; the content of sp2 carbon atom hybrid bonds and the volume ratio of the micropores are gt; the total volume of mesopores and macropores accounts for the total volume ratio. The hybrid type and the pore channel structure of the layered porous carbon layer are designed, so that the carbon-based material which is reasonable in pore structure, high in specific surface area and excellent in conductivity is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrode materials, and in particular to a layered porous carbon and a preparation method thereof and a supercapacitor. Background Art

[0002] As a new generation of storage system, supercapacitors have attracted great interest from researchers in recent years. The battery-type electrodes of supercapacitors are ion deposition / stripping processes, and the capacitive electrodes are fast physical adsorption-desorption processes. With excellent integration of high energy density and power density, supercapacitors seamlessly bridge the gap between batteries and supercapacitors, becoming one of the most viable options for future large-scale devices and portable electronic devices.

[0003] Carbon-based materials are the main capacitive electrode materials used in the field of electrochemical capacitors or supercapacitors. Carbon-based materials generally have the advantages of high specific surface area, excellent conductivity and high cycle stability, which are highly consistent with the characteristics that supercapacitor capacitive cathode materials should have. Carbon is an element in the periodic table with multiple isomers. Carbon materials involved in many industrial applications take on a variety of forms, from highly ordered crystal structures such as graphite and diamond to other less ordered varieties such as carbon fiber, activated carbon, etc.

[0004] Carbon-based materials have many advantages, such as the fact that carbon-based materials themselves have a large stock in nature, are easy to obtain, and have low cost of preparation. After a long period of research and development, carbon-based materials have become the most widely used and most mature electrode materials for commercial production. For example, the prior art CN108063057A discloses a composite porous carbon material and a method for preparing a high-power supercapacitor thereof, wherein the composite porous carbon material is composed of the following components and their weight proportions: 10-50 parts of graphene oxide, 10-50 parts of sulfide asphalt, and 20-100 parts of potassium hydroxide, which has high density, large specific surface area, and the assembled supercapacitor has high specific volume and high power. However, this carbon-based material introduces a strong alkaline substance potassium hydroxide and uses alkaline activation for chemical activation, which is not only costly but also harmful to the environment. Therefore, developing a more environmentally friendly and cost-effective preparation method is an important direction of current research.

[0005] In electrochemical performance, specific surface area and electrical conductivity are important criteria for evaluating carbon-based materials. Through a higher specific surface area, the electrode material can increase the contact area between its surface and the electrolyte, which allows the physical reversible adsorption and desorption process of ions to have more sites, thereby improving the specific capacitance of the supercapacitor. Good conductivity allows ions to diffuse more quickly, reducing the time of the reaction process, thereby improving the rate performance of the supercapacitor. In addition, a reasonable pore structure also plays an important role in the capacitance. The storage of most ions depends more on the presence of micropores in the pore structure, while the presence of mesopores and macropores in the pore structure can promote the transmission of ions.

[0006] Therefore, providing a carbon-based material with a reasonable pore structure and high conductivity, thereby achieving excellent electrochemical performance and forming a green and environmentally friendly material, has become an urgent problem to be solved. Summary of the invention

[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a layered porous carbon and a preparation method thereof and a supercapacitor. The layered porous carbon provided by the present invention forms a supercapacitor with high sp 2 Hybrid carbon materials with mesoporous and macroporous channel structures are designed with high sp 3 Hybridized carbon materials with microporous channel structures as the main components constitute carbon-based materials with reasonable pore structures, high specific surface areas and excellent electrical conductivity, which improves the electrochemical properties of layered porous carbon. At the same time, the composition of layered porous carbon is green and environmentally friendly.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a layered porous carbon, wherein the layered porous carbon comprises a first porous carbon layer and a second porous carbon layer located on the first porous carbon layer; the carbon atoms in the layered porous carbon comprise sp 3 Carbon atom hybrid bonds and sp 2 Carbon atom hybrid bonds, the pore structure of the hierarchical porous carbon includes micropores, mesopores and macropores;

[0010] In the first porous carbon layer, the sp 2 Carbon atom hybrid bond content>sp 3 Carbon atom hybrid bond content, the total volume proportion of the mesopores and the macropores>the volume proportion of the micropores;

[0011] In the second porous carbon layer, the sp 3 Carbon atom hybrid bond content>sp 2Carbon atom hybrid bond content, the volume proportion of the micropores> the total volume proportion of the mesopores and the macropores.

[0012] In the present invention, “in the first porous carbon layer, the sp 2 Carbon atom hybrid bond content>sp 3 Carbon atom hybrid bond content" and "In the second porous carbon layer, the sp 3 Carbon atom hybrid bond content>sp 2 The carbon atom hybrid bond content refers to the number of sp 3 The number of carbon atom hybrid bonds and sp 3 The relative size of the number of hybrid bonds of carbon atoms.

[0013] The layered porous carbon provided in the present invention adopts sp 2 The carbon-based material with a high proportion of carbon atom hybrid bonds is used as the first porous carbon layer, which is mainly composed of mesopores and macropores, has a large specific surface area and high conductivity. 3 The second porous carbon layer of carbon atom hybrid bonds has a pore structure with abundant micropores and a small amount of mesopores and macropores. By selecting the main hybrid type for the two-layer porous carbon layer structure and optimizing the pore structure of the porous carbon material, the specific surface area and conductivity of the layered porous carbon are improved, so that it can improve the rate performance and capacitance characteristics of the electrochemical device during application. At the same time, the presence of a large number of micropores on the surface of the special hierarchical pore structure in the layered porous carbon can improve the storage of ions in the electrochemical device during operation, thereby improving the capacitance characteristics of the electrochemical device, and the presence of mesopores and macropores can alleviate the problem of long-distance transmission of ions in the microporous channel during the operation of the electrochemical device, so that the electrochemical device has a higher rate performance. In addition, the layered porous carbon provided by the present invention is mainly designed for the pore structure and hybrid type of the first porous carbon layer and the second porous carbon layer, and the composition is green and environmentally friendly.

[0014] In the layered porous carbon provided by the present invention, the second porous carbon layer located on the surface of the first porous carbon layer is mainly distributed on the outer surface of the edge of the first porous carbon layer to cover the outer edge of the first porous carbon layer. In addition, the second porous carbon layer is also distributed on the inner surface formed by the mesopores and macropores in the first porous carbon layer.

[0015] Preferably, in the first porous carbon layer, the sp 3 The carbon atom hybrid bond content and the sp 2 The ratio of the carbon atom hybrid bond content is (1-3):(7-9), such as 1:9, 2:8 or 3:7.

[0016] In the present invention, "the sp 3 The carbon atom hybrid bond content and the sp 2 The ratio of carbon atom hybrid bond content refers to the ratio of sp 3 The number of carbon atom hybrid bonds and sp 2 The ratio of the number of hybrid bonds of carbon atoms.

[0017] Preferably, in the first porous carbon layer, the micropore volume accounts for 15-25% of the total pore volume in the first porous carbon layer, for example, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%, etc.

[0018] In the first porous carbon layer of the present invention, if sp 3 If the content of carbon atom hybrid bonds is too high and the volume of micropores accounts for too large a proportion, it will lead to an unreasonable pore size stratification structure and a small content of mesopores and macropores. In porous carbon-based materials, micropores are mainly used for storage capacity, and mesopores and macropores are mainly used for the transmission of ions inside the material. If the content of micropores is large and the content of mesopores and macropores is small, although it is beneficial to the storage capacity, it will have a greater impact on the transmission of ions, thereby significantly reducing the rate performance of the electrochemical device.

[0019] Preferably, in the second porous carbon layer, the sp 3 The carbon atom hybrid bond content and the sp 2 The ratio of the carbon atom hybrid bond content is (7-9):(1-3), such as 7:3, 8:2 or 9:1.

[0020] Preferably, in the second porous carbon layer, the micropore volume accounts for 50-60% of the total pore volume in the second porous carbon layer, for example 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, etc.

[0021] In the second porous carbon layer of the present invention, if sp 3 If the carbon atom hybridization bond is too low and the micropore volume ratio is too small, the pore structure of the layered porous carbon will be unreasonable, which will reduce the performance of the material storage capacity and thus make the specific capacitance of the electrochemical device lower.

[0022] Preferably, the mass ratio of the first porous carbon layer to the second porous carbon layer is (1-2):(4-6), for example, 1:6, 1:5, 1:4, 2:6, 2:5 or 2:4, etc.

[0023] In the present invention, if the mass ratio of the first porous carbon layer to the second porous carbon layer is too small, the second carbon layer will be excessive, the micropore volume will be too large, the mesopore and macropore volume will be too small, and the pore size hierarchy structure will be unreasonable, which will affect the effect of the layered porous carbon on ion transport during the application process, thereby causing the electrochemical performance to deteriorate; if the mass ratio of the two is too large, the first carbon layer will be excessive, the micropore volume will be too small, the mesopore and macropore volume will be too large, and the pore size hierarchy structure will be unreasonable, affecting the storage of capacity in the layered porous carbon material, thereby causing the electrochemical performance to deteriorate.

[0024] Preferably, the sp 3 The carbon atom hybrid bond content is higher than the sp 3 Carbon atom hybrid bond content.

[0025] Preferably, the volume fraction of micropores in the second porous carbon layer is higher than the volume fraction of micropores in the first porous carbon layer.

[0026] Preferably, the pore size of the micropores in the hierarchical porous carbon is 0.4-1.6 nm, for example, 0.4 nm, 0.6 nm, 0.8 nm, 1.0 nm, 1.2 nm, 1.4 nm or 1.6 nm.

[0027] The pore size of the micropores of the layered porous carbon of the present invention is regulated to be 0.4-1.6 nm, which is the active pore size range for ion storage in electrochemical devices and can exhibit more excellent rate performance during application.

[0028] Preferably, the pore size of the mesopores in the hierarchical porous carbon is 2-50 nm, for example, 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 20 nm, 30 nm, 40 nm or 50 nm.

[0029] Preferably, the pore size of the macropores in the hierarchical porous carbon is greater than 50 nm, for example, 51 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm or 80 nm.

[0030] Preferably, the carbon material in the hierarchical porous carbon is amorphous carbon.

[0031] Preferably, the layered porous carbon further comprises a doping element located in the second porous carbon layer.

[0032] Preferably, the doping element includes any one of nitrogen, phosphorus, sulfur or boron, or a combination of at least two of them.

[0033] The layered porous carbon provided by the present invention is doped with non-metallic elements such as nitrogen, phosphorus, sulfur or boron, which can further improve the conductivity of the layered porous carbon surface, thereby obtaining more excellent electrochemical performance.

[0034] Preferably, with the total mass of the layered porous carbon being 100wt%, the mass percentage of the doping element is 5-20wt%, for example, 5wt%, 8wt%, 11wt%, 14wt%, 17wt% or 20wt%.

[0035] In the present invention, if the doping amount of the doping element is too low, the conductivity of the electrode material will be too low; if the doping amount of the doping element is too high, although it will be beneficial to improve the wettability of the electrode material to the electrolyte, thereby reducing the charge transfer resistance at the electrode-electrolyte interface and improving the conductivity of the material, it will lead to excessively high pseudocapacitance and poor rate performance and stability of the electrochemical device.

[0036] In a second aspect, the present invention provides a method for preparing the layered porous carbon as described in the first aspect, the preparation method comprising:

[0037] (1) subjecting a first carbon source to a first carbonization, and then introducing an activated gas to subject a first carbon source to a second carbonization, thereby obtaining a first porous carbon layer;

[0038] (2) The first porous carbon layer, a second carbon source and a solvent are mixed, dried and then pyrolyzed to form a second porous carbon layer on the surface of the first porous carbon layer to obtain the layered porous carbon.

[0039] The preparation method provided by the present invention adopts the method of introducing active gas after carbonization for secondary carbonization, and the active gas assists in pore formation of the carbon material to form a first porous carbon layer with mainly mesopores and macropores and less micropores, thereby increasing the specific surface area of ​​the carbon-based material. The first porous carbon layer with a specific pore structure is then dispersed and mixed with a second carbon source in a solvent, and a second porous carbon layer with abundant micropores is formed on the first porous carbon layer through a process of drying and pyrolysis, thereby obtaining a layered porous carbon with a special pore structure.

[0040] The preparation method of the present invention loads a porous carbon layer with abundant micropores on a porous carbon layer mainly composed of mesopores and macropores, which can produce more adjustable micropores, retaining the characteristics of high specific surface area of ​​porous carbon and realizing the exposure of abundant micropores on the surface. The obtained layered porous carbon has a large specific surface area, a reasonable and adjustable pore structure, and excellent conductivity. When it is applied to electrochemical devices, it can improve the rate performance and capacity performance of electrochemical devices. In addition, the raw materials of the preparation method are low in price, the process is simple, the synthesis process abandons the addition of acid and base compounds, and uses active gases for pore formation, and the process is green and environmentally friendly.

[0041] Preferably, in step (1), the first carbon source comprises a biomass carbon source and / or a polymer resin.

[0042] Preferably, the biomass carbon source includes any one of asphalt, branches, corn cobs or coconut shells.

[0043] Preferably, the polymer resin includes any one of polyethylene, polypropylene or polyvinyl chloride.

[0044] Preferably, the temperature of the first carbonization in step (1) is 500-700°C, for example, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C or 700°C, etc.

[0045] Preferably, the first carbonization time in step (1) is 1-20 h, for example, 1 h, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h or 20 h.

[0046] Preferably, the activation gas in step (1) comprises water vapor and / or carbon dioxide.

[0047] In the preparation process of the first porous carbon layer in the layered porous carbon of the present invention, an activated gas is used to assist the carbonization process of the first carbon source to form pores, water vapor and / or carbon dioxide are used as the activated gas, and the introduction of alkaline solution is abandoned. The overall preparation process uses green and environmentally friendly raw materials and is environmentally friendly.

[0048] Preferably, the temperature of the second carbonization in step (1) is 500-700°C, for example, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C or 700°C, etc.

[0049] Preferably, the second carbonization time in step (1) is 1-20 h, for example, 1 h, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h or 20 h.

[0050] Preferably, in step (2), the second carbon source comprises an organic carbon source.

[0051] Preferably, the organic carbon source comprises any one or a combination of at least two of cellulose, polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, glucose, fructose, sucrose, chitosan, lactose, xylitol, thiourea, urea, melamine, p-carboxybenzenesulfonamide or p-nitroaniline.

[0052] Preferably, in step (2), the mass ratio of the first porous carbon layer to the second carbon source is 1:(1-240), for example, 1:1, 1:10, 1:20, 1:40, 1:60, 1:80, 1:100, 1:120, 1:140, 1:160, 1:180, 1:200, 1:220 or 1:240, etc.

[0053] In the present invention, if the mass ratio of the first porous carbon layer to the second carbon source is too small, the second carbon layer in the prepared layered porous carbon is excessive, the micropore volume is too large, the mesopore and macropore volume is too small, and the pore size hierarchy structure is unreasonable, thereby causing the performance of the electrochemical device to deteriorate; if the mass ratio of the first porous carbon layer to the second carbon source is too large, the first carbon layer in the prepared layered porous carbon is excessive, the micropore volume is too small, the mesopore and macropore volume is excessive, and the pore size hierarchy structure is unreasonable, thereby causing the performance of the electrochemical device to deteriorate.

[0054] Preferably, in step (2), the mass volume ratio of the first porous carbon layer to the solvent is 1g:(1-300)mL, for example, 1g:1mL, 1g:3mL, 1g:5mL, 1g:10mL, 1g:30mL, 1g:50mL, 1g:100mL, 1g:150mL, 1g:200mL, 1g:250mL or 1g:300mL, etc., preferably 1g:(50-150)mL.

[0055] In the present invention, a solvent is added during the mixing process of the first porous carbon layer and the second carbon source in order to dissolve the reaction materials and facilitate sufficient mixing. When the mass-to-volume ratio of the first porous carbon layer to the solvent is too small and the amount of solvent added is too much, the subsequent drying time will be too long, the solvent will be difficult to completely remove, and the pore size will be destroyed. Problems; when the mass-to-volume ratio of the first porous carbon layer to the solvent is too large and the amount of solvent added is too little, the reaction materials will not be fully dissolved during the mixing process.

[0056] Preferably, the solvent in step (2) comprises any one of water, ethanol, isopropanol or acetone, or a combination of at least two of them.

[0057] Preferably, the mixing temperature in step (2) is 30-80°C, such as 30°C, 40°C, 50°C, 60°C, 70°C or 80°C.

[0058] Preferably, the mixing time in step (2) is 0.5-3 h, for example 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0059] Preferably, the mixing in step (2) is carried out under oil bath conditions.

[0060] Preferably, a compound containing a doping element is also added during the mixing process in step (2).

[0061] In the present invention, the amount of the compound containing the doping element added in the mixing process of step (2) is determined based on "the total mass of the layered porous carbon is 100wt%, and the mass percentage of the doping element is 5-20wt%" in the obtained layered porous carbon. Most of the compounds containing the doping element will volatilize and decompose during the pyrolysis reaction with the second carbon source and the first porous carbon layer. Therefore, it is necessary to add an excess amount of the compound containing the doping element during the mixing process.

[0062] Optionally, the mass ratio of the second carbon source to the compound containing the doping element is (1-20):(1-20), wherein the mass fraction of the second carbon source can be selected as "1-20", for example, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18 or 20; the mass fraction of the compound containing the doping element can be selected as "1-20", for example, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18 or 20.

[0063] Among the "compounds containing doping elements" used in the present invention, some compounds also contain a large amount of carbon and oxygen elements, which can provide carbon materials for the preparation of the second porous carbon layer.

[0064] Preferably, the compound containing the doping element includes any one of a nitrogen-containing compound, a sulfur-containing compound, a phosphorus-containing compound or a boron-containing compound, or a combination of at least two thereof.

[0065] Preferably, the nitrogen-containing compound includes any one of thiourea, urea, melamine, p-nitroaniline, benzidine, pyrrolidine or 2-naphthylamine, or a combination of at least two thereof.

[0066] Preferably, the sulfur-containing compound includes any one of p-carboxybenzenesulfonamide, rosiglitazone, 2-thiopheneacetic acid or thiourea, or a combination of at least two thereof.

[0067] Preferably, the phosphorus-containing compound includes any one of phosphate, hydrogen phosphate or phospholipid, or a combination of at least two of them.

[0068] Preferably, the boron-containing compound includes any one of boric acid, tetraboric acid, sodium tetraborate or boron carbide, or a combination of at least two thereof.

[0069] Preferably, the drying method in step (2) is any one of oven drying, vacuum drying or freeze drying.

[0070] Preferably, the pyrolysis atmosphere in step (2) is any one of a nitrogen atmosphere, a hydrogen atmosphere or an inert gas atmosphere, or a combination of at least two of them.

[0071] Preferably, the pyrolysis in step (2) includes a first pyrolysis stage and a second pyrolysis stage.

[0072] Preferably, the temperature of the first pyrolysis stage is 200-400°C, for example, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C or 400°C, etc.

[0073] In the present invention, if the temperature of the first pyrolysis stage is too low, the decomposition temperature of the second carbon source cannot be reached; if the temperature of the first pyrolysis stage is too high, the structure of the carbon material is destroyed during the pyrolysis process.

[0074] Preferably, the time of the first pyrolysis stage is 0.5-6 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h or 6 h, etc.

[0075] Preferably, the temperature of the second pyrolysis stage is 500-1000°C, such as 500°C, 600°C, 700°C, 800°C, 900°C or 1000°C.

[0076] In the present invention, if the temperature of the second pyrolysis stage is too low, the proportion of micropores in the second porous carbon layer will be small, and even amorphous carbon cannot be formed; if the temperature of the second pyrolysis stage is too high, the proportion of micropores in the second porous carbon layer will be too large, and even the structure of the obtained carbon-based material will be destroyed during the pyrolysis process.

[0077] Preferably, the second pyrolysis stage lasts for 8-10 h, such as 8 h, 8.5 h, 9 h, 9.5 h or 10 h.

[0078] In a third aspect, the present invention provides a supercapacitor, comprising a positive electrode material, wherein the positive electrode material comprises the layered porous carbon as described in the first aspect.

[0079] The supercapacitor provided by the present invention adopts layered porous carbon as the active material in the positive electrode material. The specific layout of the hybridization mode and the unique hierarchical pore structure in the layered porous carbon are beneficial to the ion storage in the supercapacitor. At the same time, it can alleviate the problem of long-distance transmission of ions in the microporous channels in the supercapacitor, thereby improving the electrochemical performance of the supercapacitor.

[0080] Preferably, the positive electrode material further includes a conductive agent, a binder, a solvent and a current collector.

[0081] In the present invention, the conductive agent in the positive electrode material is not specifically limited, and includes but is not limited to conductive carbon black, Ketjen black or acetylene black, and those skilled in the art can select it according to needs.

[0082] In the present invention, the binder in the positive electrode material is not specifically limited, and includes but is not limited to polyvinylidene fluoride or carboxymethyl cellulose, and those skilled in the art can select it according to needs.

[0083] In the present invention, the solvent in the positive electrode material is not specifically limited, including but not limited to N-methylpyrrolidone or water, and those skilled in the art can select it according to needs.

[0084] In the present invention, the current collector in the positive electrode material is not specifically limited, including but not limited to stainless steel mesh, titanium foil or carbon paper, and those skilled in the art can select it according to needs.

[0085] Preferably, the supercapacitor further comprises a negative electrode, an electrolyte, a diaphragm, a gasket, a spring and an electrode shell.

[0086] Preferably, the negative electrode includes any one of a zinc negative electrode, a lithium negative electrode or a sodium negative electrode.

[0087] Compared with the prior art, the present invention has at least the following beneficial effects:

[0088] (1) The layered porous carbon provided by the present invention forms a high sp 2 Hybrid carbon materials with mesoporous and macroporous channel structures are designed with high sp 3 Hybridized carbon materials with microporous channel structures as the main components constitute carbon-based materials with reasonable pore structures, high specific surface areas and excellent electrical conductivity, which improves the electrochemical properties of layered porous carbon. At the same time, the composition of layered porous carbon is green and environmentally friendly.

[0089] (2) The preparation method of the present invention can produce more adjustable micropores by mixing an organic carbon source on a porous carbon layer mainly composed of mesopores and macropores, and then drying and pyrolyzing the porous carbon layer with rich micropores, which not only retains the characteristics of high specific surface area of ​​porous carbon, but also realizes the exposure of rich micropores on the surface. The obtained layered porous carbon has a large specific surface area, a reasonable and adjustable pore structure, and excellent conductivity. When it is applied to electrochemical devices, it can improve the rate performance and capacity performance of electrochemical devices. In addition, the raw materials of the preparation method are low in price, the process is simple, and the synthesis process abandons the addition of acid and base compounds, and uses active gases for pore formation. The process is green and environmentally friendly.

[0090] (3) The supercapacitor in the present invention uses layered porous carbon as the active material in the positive electrode material. The specific layout of the hybridization mode and the unique hierarchical pore structure in the layered porous carbon are beneficial to the ion storage in the supercapacitor. At the same time, it can alleviate the problem of long-distance transmission of ions in the microporous channels in the supercapacitor, thereby improving the electrochemical performance of the supercapacitor. BRIEF DESCRIPTION OF THE DRAWINGS

[0091] Figure 1 It is a schematic diagram of the cross-sectional structure of layered porous carbon provided by a specific embodiment of the present invention.

[0092] Figure 2 It is a schematic diagram of the cross-sectional structure of porous carbon provided by a specific embodiment of the present invention.

[0093] Among them, 1, the first porous carbon layer; 2, the second porous carbon layer.

[0094] Figure 3 3 is a pore size distribution diagram of the layered porous carbon of Example 1 and the porous carbon of Comparative Example 1.

[0095] Figure 4 3 is a rate performance diagram of the supercapacitors of Application Example 1 and Comparative Application Example 1. DETAILED DESCRIPTION

[0096] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0097] Example 1

[0098] This embodiment provides a layered porous carbon, and its cross-sectional structure schematic diagram is as follows Figure 1 As shown, the layered porous carbon comprises a first porous carbon layer 1, a second porous carbon layer 2 located on the surface of the first porous carbon layer 1, and nitrogen and sulfur elements doped in the second porous carbon layer. The composition of the layered porous carbon is amorphous carbon. The carbon atoms in the first porous carbon layer 1 and the second porous carbon layer 2 both include sp 3 Carbon atom hybrid bonds and sp 2 Carbon atom hybrid bonds, the pore structures in the first porous carbon layer 1 and the second porous carbon layer 2 both include micropores, mesopores and macropores, a portion of the second porous carbon layer 2 is coated on the surface of the outer edge of the first porous carbon layer 1, and a portion is located on the surface of the mesopores and macropores in the first porous carbon layer 1, and the mass ratio of the first porous carbon layer 1 to the second porous carbon layer 2 is 1:4. In the first porous carbon layer 1, sp 3 Carbon atom hybrid bond content and sp 2The ratio of the carbon atom hybrid bond content is 2:8, the pore size of the micropore is 0.4-1nm, the pore size of the mesopore is 2.5-50nm, and the pore size of the macropore is 50-100nm, excluding 50nm, and the volume of the micropore accounts for 18% of the total pore volume in the first porous carbon layer 1; in the second porous carbon layer 2, sp 3 Carbon atom hybrid bond content and sp 2 The ratio of the content of hybrid bonds of carbon atoms is 9:1, the pore size of micropores is 0.6-1nm, the pore size of mesopores is 2.6-50nm, the pore size of macropores is 50-100nm, excluding 50nm, and the volume of micropores accounts for 56% of the total pore volume in the second porous carbon layer 2; the total mass of the layered porous carbon is 100wt%, the total amount of doped nitrogen and sulfur elements is 15wt%, and the molar ratio of nitrogen and sulfur elements is 2:1.

[0099] This embodiment also provides a method for preparing the above-mentioned layered porous carbon, and the preparation method comprises the following steps:

[0100] (1) The asphalt is placed at 600°C for 5 hours for a first carbonization, and then water vapor is introduced to assist pore formation, and a second carbonization is carried out at 600°C for 5 hours to obtain a first porous carbon layer.

[0101] (2) Take 100 mg of the first porous carbon layer obtained in step (1), 500 mg of chitosan and 5 g of thiourea, mix them, disperse them in 12 mL of deionized water, mix them in an oil bath at 80°C for 1.5 h, then vacuum dry the mixed product for 12 h to completely remove the solvent, pyrolyze the dried product at 250°C for 5 h in a nitrogen atmosphere, and then pyrolyze it at 850°C for 8 h to form a second porous carbon layer on the surface of the first porous carbon layer, collect black powder, and prepare layered porous carbon.

[0102] Example 2

[0103] This embodiment provides a layered porous carbon, and its cross-sectional structure schematic diagram is as follows Figure 1 As shown, the layered porous carbon comprises a first porous carbon layer 1, a second porous carbon layer 2 located on the surface of the first porous carbon layer 1, and a boron element doped in the second porous carbon layer. The composition of the layered porous carbon is amorphous carbon. The carbon atoms in the first porous carbon layer 1 and the second porous carbon layer 2 both include sp 3 Carbon atom hybrid bonds and sp 2 Carbon atom hybrid bonds, the pore structures in the first porous carbon layer 1 and the second porous carbon layer 2 both include micropores, mesopores and macropores, a portion of the second porous carbon layer 2 is coated on the surface of the outer edge of the first porous carbon layer 1, and a portion is located on the surface of the mesopores and macropores in the first porous carbon layer 1, and the mass ratio of the first porous carbon layer 1 to the second porous carbon layer 2 is 1:5. In the first porous carbon layer 1, sp 3Carbon atom hybrid bond content and sp 2 The ratio of the carbon atom hybrid bond content is 1:9, the pore size of the micropore is 0.5-1.5nm, the pore size of the mesopore is 2.6-50nm, and the pore size of the macropore is 50-100nm, excluding 50nm, and the volume of the micropore accounts for 17% of the total pore volume in the first porous carbon layer 1; in the second porous carbon layer 2, sp 3 Carbon atom hybrid bond content and sp 2 The ratio of the content of hybrid bonds of carbon atoms is 7:3. The pore structure of the second porous carbon layer 2 includes micropores, mesopores and macropores. The pore diameter of the micropores is 0.6-1.6nm, the pore diameter of the mesopores is 2.6-50nm, the pore diameter of the macropores is 50-100nm, excluding 50nm, and the volume of the micropores accounts for 51% of the total pore volume in the second porous carbon layer 2; the total mass of the layered porous carbon is 100wt%, and the mass percentage of the doped boron element is 10wt%.

[0104] This embodiment also provides a method for preparing the above-mentioned layered porous carbon, and the preparation method comprises the following steps:

[0105] (1) The corn cob was placed at 500°C for 2 hours for a first carbonization, and then water vapor was introduced to assist pore formation, and a second carbonization was performed at 500°C for 18 hours to obtain a first porous carbon layer.

[0106] (2) Take 100 mg of the first porous carbon layer obtained in step (1), 800 mg of fructose and 9 g of boric acid, mix them, disperse them in 9 mL of ethanol, mix them in an oil bath at 50°C for 2 h, then vacuum dry the mixed product for 12 h to completely remove the solvent, pyrolyze the dried product at 200°C for 6 h in a nitrogen atmosphere, and then pyrolyze it at 500°C for 10 h to form a second porous carbon layer coated on the first porous carbon layer, collect black powder, and prepare layered porous carbon.

[0107] Example 3

[0108] This embodiment provides a layered porous carbon, and its cross-sectional structure schematic diagram is as follows Figure 1 As shown, the layered porous carbon comprises a first porous carbon layer 1, a second porous carbon layer 2 located on the surface of the first porous carbon layer 1, and nitrogen doped in the second porous carbon layer. The composition of the layered porous carbon is amorphous carbon. The carbon atoms in the first porous carbon layer 1 and the second porous carbon layer 2 both include sp 3 Carbon atom hybrid bonds and sp 2Carbon atom hybrid bonds, the pore structures in the first porous carbon layer 1 and the second porous carbon layer 2 both include micropores, mesopores and macropores, a portion of the second porous carbon layer 2 is coated on the surface of the outer edge of the first porous carbon layer 1, and a portion is located on the surface of the mesopores and macropores in the first porous carbon layer 1, and the mass ratio of the first porous carbon layer 1 to the second porous carbon layer 2 is 1:4. In the first porous carbon layer 1, sp 3 Carbon atom hybrid bond content and sp 2 The ratio of the carbon atom hybrid bond content is 3:7, the pore size of the micropore is 0.5-1nm, the pore size of the mesopore is 6-50nm, and the pore size of the macropore is 50-100nm, excluding 50nm, and the volume of the micropore accounts for 24% of the total pore volume in the first porous carbon layer 1; in the second porous carbon layer 2, sp 3 Carbon atom hybrid bond content and sp 2 The ratio of the hybrid bond content of carbon atoms is 9:1, the pore size of the micropores is 0.6-1nm, the pore size of the mesopores is 8-50nm, the pore size of the macropores is 50-100nm, excluding 50nm, and the volume of the micropores accounts for 62% of the total pore volume in the second porous carbon layer 2; the total mass of the layered porous carbon is 100wt%, and the mass percentage of the doped nitrogen element is 8wt%.

[0109] This embodiment also provides a method for preparing the above-mentioned layered porous carbon, and the preparation method comprises the following steps:

[0110] (1) The coconut shell was placed at 700°C for 7 hours for the first carbonization, and then water vapor was introduced to assist pore formation, and the second carbonization was carried out at 700°C for 14 hours to obtain the first porous carbon layer.

[0111] (2) Take 150 mg of the first porous carbon layer obtained in step (1), 800 mg of lactose and 10 g of urea, mix them, disperse them in 15 mL of isopropanol, mix them in an oil bath at 70°C for 0.5 h, then vacuum dry the mixed product for 12 h to completely remove the solvent, pyrolyze the dried product at 300°C for 3 h in a nitrogen atmosphere, and then pyrolyze it at 1000°C for 9 h to form a second porous carbon layer coated on the first porous carbon layer, collect black powder, and prepare layered porous carbon.

[0112] Example 4

[0113] This embodiment provides a layered porous carbon, and its cross-sectional structure schematic diagram is as follows Figure 1 As shown, the layered porous carbon comprises a first porous carbon layer 1, a second porous carbon layer 2 located on the surface of the first porous carbon layer 1, and phosphorus doped in the second porous carbon layer. The composition of the layered porous carbon is amorphous carbon. The carbon atoms in the first porous carbon layer 1 and the second porous carbon layer 2 both comprise sp 3 Carbon atom hybrid bonds and sp 2Carbon atom hybrid bonds, the pore structures in the first porous carbon layer 1 and the second porous carbon layer 2 both include micropores, mesopores and macropores, a portion of the second porous carbon layer 2 is coated on the surface of the outer edge of the first porous carbon layer 1, and a portion is located on the surface of the mesopores and macropores in the first porous carbon layer 1, and the mass ratio of the first porous carbon layer 1 to the second porous carbon layer 2 is 2:4. In the first porous carbon layer 1, sp 3 Carbon atom hybrid bond content and sp 2 The ratio of the carbon atom hybrid bond content is 2:8, the pore size of the micropore is 0.7-1nm, the pore size of the mesopore is 13-50nm, and the pore size of the macropore is 50-100nm, excluding 50nm, and the volume of the micropore accounts for 20% of the total pore volume in the first porous carbon layer 1; in the second porous carbon layer 2, sp 3 Carbon atom hybrid bond content and sp 2 The ratio of the hybrid bond content of carbon atoms is 8:2, the pore size of the micropores is 0.9-1nm, the pore size of the mesopores is 13-50nm, the pore size of the pores is 50-100nm, excluding 50nm, and the volume of the micropores accounts for 54% of the total pore volume in the second porous carbon layer 2; the total mass of the layered porous carbon is 100wt%, and the mass percentage of the doped phosphorus element is 5wt%.

[0114] This embodiment also provides a method for preparing the above-mentioned layered porous carbon, and the preparation method comprises the following steps:

[0115] (1) The dendrites were subjected to a first carbonization at 550° C. for 10 h, and then carbon dioxide gas was introduced to assist pore formation, followed by a second carbonization at 550° C. for 10 h to obtain a first porous carbon layer.

[0116] (2) Take 100 mg of the first porous carbon layer obtained in step (1), 400 mg of cellulose and 8 g of sodium hypophosphite, mix them, disperse them in 12 mL of acetone, mix them in an oil bath at 75°C for 1 hour, then vacuum dry the mixed product for 12 hours to completely remove the solvent, pyrolyze the dried product at 400°C for 1 hour in a hydrogen atmosphere, and then pyrolyze it at 800°C for 10 hours to form a second porous carbon layer coated on the first porous carbon layer, collect black powder, and prepare layered porous carbon.

[0117] Example 5

[0118] This embodiment provides a layered porous carbon, and its cross-sectional structure schematic diagram is as follows Figure 1 As shown, the layered porous carbon comprises a first porous carbon layer 1, a second porous carbon layer 2 located on the surface of the first porous carbon layer 1, and nitrogen and boron elements doped in the second porous carbon layer. The composition of the layered porous carbon is amorphous carbon. The carbon atoms in the first porous carbon layer 1 and the second porous carbon layer 2 both include sp 3 Carbon atom hybrid bonds and sp2 Carbon atom hybrid bonds, the pore structures in the first porous carbon layer 1 and the second porous carbon layer 2 both include micropores, mesopores and macropores, a portion of the second porous carbon layer 2 is coated on the surface of the outer edge of the first porous carbon layer 1, and a portion is located on the surface of the mesopores and macropores in the first porous carbon layer 1, and the mass ratio of the first porous carbon layer 1 to the second porous carbon layer 2 is 2:4. In the first porous carbon layer 1, sp 3 Carbon atom hybrid bond content and sp 2 The ratio of the carbon atom hybrid bond content is 2:8, the pore size of the micropore is 0.6-1nm, the pore size of the mesopore is 3-50nm, and the pore size of the macropore is 50-100nm, excluding 50nm, and the volume of the micropore accounts for 22% of the total pore volume in the first porous carbon layer 1; in the second porous carbon layer 2, sp 3 Carbon atom hybrid bond content and sp 2 The ratio of the content of hybrid bonds of carbon atoms is 9:1, the pore size of micropores is 0.7-1nm, the pore size of mesopores is 3-50nm, the pore size of macropores is 50-100nm, excluding 50nm, and the volume of micropores accounts for 57% of the total pore volume in the second porous carbon layer 2; the total mass of the layered porous carbon is 100wt%, the mass percentage of doped nitrogen and boron elements is 13wt%, and the molar ratio of nitrogen and boron elements is 3:2.

[0119] This embodiment also provides a method for preparing the above-mentioned layered porous carbon, and the preparation method comprises the following steps:

[0120] (1) The coconut shell was subjected to a first carbonization at 650°C for 20 h, and then carbon dioxide gas was introduced to assist pore formation, and a second carbonization was carried out at 650°C for 13 h to obtain a first porous carbon layer.

[0121] (2) Take 100 mg of the first porous carbon layer obtained in step (1), 500 mg of glucose, 5 g of boric acid and 7 g of p-nitroaniline, mix them, disperse them in 15 mL of isopropanol, mix them in an oil bath at 40°C for 3 h, then vacuum dry the mixed product for 12 h to completely remove the solvent, pyrolyze the dried product at 200°C for 6 h in an argon atmosphere, and then pyrolyze it at 900°C for 8 h to form a second porous carbon layer coated on the first porous carbon layer, collect black powder, and prepare layered porous carbon.

[0122] Example 6

[0123] The difference between this embodiment and embodiment 1 is that in the layered porous carbon provided in this embodiment, the mass ratio of the first porous carbon layer 1 to the second porous carbon layer 2 is 2:3. The rest of the contents are the same as those in embodiment 1.

[0124] Example 7

[0125] The difference between this embodiment and embodiment 1 is that in the layered porous carbon provided in this embodiment, the mass ratio of the first porous carbon layer 1 to the second porous carbon layer 2 is 1:6. The rest of the contents are the same as those in embodiment 1.

[0126] Example 8

[0127] The difference between this embodiment and embodiment 1 is that in the layered porous carbon provided in this embodiment, the total mass of the layered porous carbon is 100wt%, and the total mass percentage of the doped nitrogen element and sulfur element is 4wt%. The rest of the contents are the same as those in embodiment 1.

[0128] Example 9

[0129] The difference between this embodiment and embodiment 1 is that in the layered porous carbon provided in this embodiment, the total mass of the layered porous carbon is 100wt%, and the total mass percentage of the doped nitrogen element and sulfur element is 25wt%. The rest of the contents are the same as those in embodiment 1.

[0130] Example 10

[0131] The difference between this embodiment and embodiment 1 is that the layered porous carbon provided in this embodiment lacks doped nitrogen and sulfur elements. The rest of the contents are the same as those in embodiment 1.

[0132] Embodiment 11

[0133] The difference between this embodiment and embodiment 1 is that in step (2) of the method for preparing layered porous carbon provided in this embodiment, the amount of deionized water added is 3 mL. The rest of the contents are the same as those in embodiment 1.

[0134] Example 12

[0135] The difference between this embodiment and embodiment 1 is that in step (2) of the method for preparing layered porous carbon provided in this embodiment, the amount of deionized water added is 20 mL. The rest of the contents are the same as those in embodiment 1.

[0136] Embodiment 13

[0137] The difference between this embodiment and embodiment 1 is that in the method for preparing hierarchical porous carbon provided in this embodiment, the addition of activation gas water vapor is omitted in step (1), and the asphalt is only carbonized at 600° C. for 10 hours. The rest of the contents are the same as those in embodiment 1.

[0138] Embodiment 14

[0139] The difference between this embodiment and embodiment 1 is that in the method for preparing layered porous carbon provided in this embodiment, the temperature of the first pyrolysis stage is replaced with 100° C. The rest of the contents are the same as those in embodiment 1.

[0140] Embodiment 15

[0141] The difference between this embodiment and embodiment 1 is that in the method for preparing layered porous carbon provided in this embodiment, the temperature of the first pyrolysis stage is replaced with 500° C. The rest of the contents are the same as those in embodiment 1.

[0142] Example 16

[0143] The difference between this embodiment and embodiment 1 is that in the first porous carbon layer 1 of the layered porous carbon provided in this embodiment, sp 3 Carbon atom hybrid bond content and sp 2 The ratio of the carbon atom hybrid bond content is 4:6, and the volume of the micropores accounts for 30% of the total pore volume in the first porous carbon layer 1; accordingly, in the preparation method provided in this embodiment, step (1) is to place the asphalt at 850°C for 5 hours for the first carbonization, and then introduce water vapor to assist pore formation, and then perform the second carbonization at 850°C for 5 hours to obtain the first porous carbon layer. The rest of the contents are the same as in Example 1.

[0144] Embodiment 17

[0145] The difference between this embodiment and embodiment 1 is that in the second porous carbon layer 2 of the layered porous carbon provided in this embodiment, sp 3 Carbon atom hybrid bond content and sp 2 The ratio of the carbon atom hybrid bond content is 6:4, and the volume of the micropores accounts for 40% of the total pore volume in the second porous carbon layer 2; accordingly, in the preparation method provided in this embodiment, step (2) is to pyrolyze the dried product at 250°C for 5h under a nitrogen atmosphere, and then pyrolyze it at 400°C for 8h to form a second porous carbon layer coated on the first porous carbon layer, collect black powder, and prepare layered porous carbon. The rest of the content is the same as in Example 1.

[0146] Embodiment 18

[0147] The difference between this embodiment and embodiment 1 is that in the second porous carbon layer 2 of the layered porous carbon provided in this embodiment, sp 3 Carbon atom hybrid bond content and sp 2 The ratio of the carbon atom hybrid bond content is 9.5:0.5, and the volume of the micropores accounts for 70% of the total pore volume in the second porous carbon layer 2; accordingly, in the preparation method provided in this embodiment, step (2) is to pyrolyze the dried product at 250°C for 5h under a nitrogen atmosphere, and then pyrolyze it at 1200°C for 8h to form a second porous carbon layer coated on the first porous carbon layer, collect black powder, and prepare layered porous carbon. The rest of the content is the same as in Example 1.

[0148] Comparative Example 1

[0149] The difference between this comparative example and Example 1 is that the porous carbon provided in this comparative example is only the first porous carbon layer 1, and lacks the second porous carbon layer 2 located on the surface of the first porous carbon layer 1. The schematic diagram of its cross-sectional structure is shown in FIG. Figure 2 As shown; accordingly, the preparation method provided in this comparative example only adopts step (1) to prepare the first porous carbon layer as the carbon-based material. The rest of the contents are the same as those in Example 1.

[0150] Comparative Example 2

[0151] The difference between this comparative example and Example 2 is that the porous carbon provided in this comparative example is only the first porous carbon layer 1, and lacks the second porous carbon layer 2 located on the surface of the first porous carbon layer 1. The schematic diagram of its cross-sectional structure is shown in FIG. Figure 2 As shown; accordingly, the preparation method provided in this comparative example only adopts step (1) to prepare the first porous carbon layer as the carbon-based material. The rest of the contents are the same as those in Example 2.

[0152] Comparative Example 3

[0153] The difference between this comparative example and Example 3 is that the porous carbon provided in this comparative example is only the first porous carbon layer 1, and lacks the second porous carbon layer 2 located on the surface of the first porous carbon layer 1. The schematic diagram of its cross-sectional structure is shown in FIG. Figure 2 Accordingly, the preparation method provided in this comparative example only adopts step (1) to prepare the first porous carbon layer as the carbon-based material. The rest of the contents are the same as those in Example 3.

[0154] Comparative Example 4

[0155] The difference between this comparative example and Example 4 is that the porous carbon provided in this comparative example is only the first porous carbon layer 1, and lacks the second porous carbon layer 2 located on the surface of the first porous carbon layer 1. The schematic diagram of its cross-sectional structure is shown in FIG. Figure 2 Accordingly, the preparation method provided in this comparative example only adopts step (1) to prepare the first porous carbon layer as the carbon-based material. The rest of the contents are the same as those in Example 4.

[0156] Comparative Example 5

[0157] The difference between this comparative example and Example 5 is that the porous carbon provided in this comparative example is only the first porous carbon layer 1, and lacks the second porous carbon layer 2 located on the surface of the first porous carbon layer 1. The schematic diagram of its cross-sectional structure is shown in FIG. Figure 2 Accordingly, the preparation method provided in this comparative example only adopts step (1) to prepare the first porous carbon layer as the carbon-based material. The rest of the contents are the same as those in Example 5.

[0158] Comparative Example 6

[0159] The difference between this comparative example and Example 1 is that the porous carbon provided in this comparative example only has a second porous carbon layer, and the second porous carbon layer is directly used as the carbon-based material.

[0160] Accordingly, the preparation method provided in this comparative example is as follows:

[0161] 500 mg of chitosan and 5 g of thiourea were mixed, dispersed in 12 mL of deionized water, and mixed in an oil bath at 80°C for 1.5 h. The mixed product was then vacuum dried for 12 h to completely remove the solvent. In a nitrogen atmosphere, the dried product was pyrolyzed at 250°C for 5 h and then at 1000°C for 8 h to form a second porous carbon layer, thereby preparing porous carbon.

[0162] The rest of the contents are the same as those in Example 1.

[0163] Application Example 1-18 and Comparative Application Example 1-6

[0164] 80 mg of the layered porous carbon provided in Example 1-18 and the porous carbon provided in Comparative Example 1-6 were mixed with 10 mg of conductive carbon black and 10 mg of polyvinylidene fluoride, respectively, and 800 μL of N-methylpyrrolidone was added as a solvent, stirred for 30 min, and a positive electrode slurry was obtained, and then, a scraper was used to evenly coat the titanium foil current collector with a coating thickness of 18 μm. After that, it was vacuum dried and taken out after being left overnight at a temperature of 60 ° C. A circular battery pole piece with a diameter of 12 mm was cut into a slicer as the positive electrode of the supercapacitor, and a metal zinc with a diameter of 12 mm was cut as the negative electrode disc. In a CR2032 button battery, the electrode shell, positive electrode sheet, diaphragm, negative electrode sheet, gasket, shrapnel, and electrode shell were assembled in the order of assembly, and 80 μL of electrolyte was dripped between the diaphragm and the pole piece, and the electrolyte composition was 3 mol / L Zn(CF3SO3)2, and finally assembled to obtain a supercapacitor.

[0165] The supercapacitors provided in Application Examples 1-18 and Comparative Application Examples 1-6 were heated at 0.2V-1.8V and 0.1Ag -1 , 0.5A g -1 , 1A g -1 , 5A g -1 , 10A g -1 , 0.1A g -1 The battery was charged and discharged for 10 cycles at a current density of , and the discharge specific capacitance was recorded and calculated. The test results are shown in Table 1 below.

[0166] Table 1

[0167]

[0168]

[0169] The test results show that:

[0170] (1) It can be seen from Application Examples 1 to 5 that the layered porous carbon provided by the present invention has a high sp 2 Hybrid carbon materials are mainly composed of mesoporous and macroporous channel structures, with high sp 3 Hybrid carbon materials, which are mainly based on microporous channel structures, form carbon-based materials with reasonable pore structures, high specific surface area and excellent conductivity, which improves the electrochemical properties of layered porous carbon. At the same time, the composition of layered porous carbon is green and environmentally friendly.

[0171] (2) By comparing Application Example 1 with Application Examples 6-7, it can be seen that in the present invention, if the mass ratio of the first porous carbon layer to the second porous carbon layer is too small, the second porous carbon layer will be excessive, the micropore volume will be too large, the mesopore and macropore volume will be too small, and the pore size hierarchy structure will be unreasonable, which will affect the effect of the layered porous carbon on ion transport during the application process, thereby causing the electrochemical performance to deteriorate; if the mass ratio of the two is too large, the first porous carbon layer will be excessive, the micropore volume will be too small, the mesopore and macropore volume will be too large, which will also make the pore size hierarchy structure unreasonable, affecting the storage of capacity in the layered porous carbon material, thereby causing the electrochemical performance to deteriorate.

[0172] (3) By comparing Application Example 1 with Application Examples 8-9, it can be seen that if the doping amount of the doping element in the present invention is too low, the conductivity of the electrode material will be too low; if the doping amount of the doping element is too high, although it will be beneficial to improve the wettability of the electrode material to the electrolyte and can improve the conductivity of the material, it will lead to excessively high pseudocapacitance and poor rate performance and stability of the electrochemical device.

[0173] (4) By comparing Application Example 1 and Application Example 10, it can be seen that by doping the layered porous carbon of the present invention with non-metallic elements, the conductivity of the layered porous carbon surface can be further improved, thereby making the rate performance of the assembled supercapacitor more excellent.

[0174] (5) By comparing Application Example 1 with Application Examples 11-12, it can be seen that if the amount of solvent added in the present invention is too little, the reaction materials will not be fully dissolved during the mixing process; if the amount of solvent added is too much, the subsequent drying time will be too long, the solvent will be difficult to completely remove, and the pore size will be destroyed.

[0175] (6) By comparing Application Example 1 and Application Example 13, it can be seen that if the present invention omits the use of activated gas to assist in pore formation of the asphalt biomass carbon source, the content of mesopores and macropores in the first porous carbon layer will be too low, thereby reducing the performance of the electrochemical device.

[0176] (7) By comparing Application Example 1 with Application Examples 14-15, it can be seen that if the temperature of the first pyrolysis stage of the present invention is too low, the decomposition temperature of the second carbon source cannot be reached, affecting the electrochemical properties of the carbon-based material; if the temperature of the first pyrolysis stage is too high, the structure of the carbon-based material is destroyed during the pyrolysis process, resulting in poor rate performance of the obtained material and a decrease in specific capacitance.

[0177] (8) By comparing Application Example 1 with Application Example 16, it can be seen that in the first porous carbon layer of the present invention, if sp 3 If the carbon atom hybrid bonds are too high and the micropore volume accounts for too large a proportion, it will lead to an unreasonable pore size stratification structure. Although it is beneficial to the storage capacity, it will have a greater impact on the transmission of ions, thereby significantly deteriorating the rate performance of the electrochemical device.

[0178] (9) By comparing Application Example 1 with Application Examples 17-18, it can be seen that in the second porous carbon layer of the present invention, if sp 3 If the carbon atom hybrid bond is too low and the micropore volume ratio is too small, the specific capacitance of the supercapacitor will be too low. 3 If the carbon atom hybrid bonds are too high and the micropore volume accounts for too large a proportion, the rate performance of the supercapacitor will deteriorate.

[0179] (10) By comparing Application Example 1 with Comparative Application Example 1, Application Example 2 with Comparative Application Example 2, Application Example 3 with Comparative Application Example 3, Application Example 4 with Comparative Application Example 4, and Application Example 5 with Comparative Application Example 5, it can be seen that if the porous carbon material provided by the present invention lacks a second porous carbon layer, the pore size in the pore structure of the carbon-based material is generally too large, which is not conducive to the transmission of metal ions, thereby causing the rate performance of the assembled supercapacitor to deteriorate.

[0180] Figure 3 The pore size distribution diagrams of the layered porous carbon of Example 1 and the porous carbon of Comparative Example 1 are given. It can be seen from the diagram that, compared with the porous carbon material provided in the Comparative Example which consists of only the first porous carbon layer, Example 1 loads the second porous carbon layer on the surface of the first porous carbon layer, so that the micropore volume of the layered porous carbon is greatly increased, and the micropore diameters are concentrated in a specific range, which are active pore diameters for ion storage, which is beneficial for the supercapacitor to provide more adsorption sites when adsorbing ions, thereby storing more charges.

[0181] Figure 4The rate performance diagrams of the supercapacitors of Application Example 1 and Comparative Application Example 1 are given. It can be seen from the figure that the discharge specific capacitance of the layered porous carbon in Application Example 1 at each current density is significantly higher than that of the porous carbon material composed of only the first porous carbon layer provided in Comparative Application Example 1. The supercapacitor of Application Example 1 has a discharge specific capacitance of 0.1A g -1 The discharge specific capacitance is 110.3Fg -1 , compared with the supercapacitor of Application Example 1 at 0.1A g -1 The discharge specific capacitance is only 57.2F g -1 , even at 10A g -1 At high current density, the supercapacitor in Application Example 1 also has 44.8F g -1 The discharge specific capacitance.

[0182] (11) It can be seen from the comparison between Application Example 1 and Comparative Application Example 6 that if the porous carbon material provided by the present invention lacks the first porous carbon layer and only uses the second porous carbon layer as the carbon-based material, it will lead to a lack of sufficient mesopores and macropores, resulting in poor performance of the supercapacitor.

[0183] In summary, the layered porous carbon provided in the present invention adopts sp 2 The carbon-based material with a high proportion of carbon atom hybrid bonds is used as the first porous carbon layer, which is mainly composed of mesopores and macropores, has a large specific surface area and high conductivity. 3 The second porous carbon layer of carbon atom hybrid bonds has a pore structure with abundant micropores and a small amount of mesopores and macropores. By selecting the main hybrid type for the two-layer porous carbon layer structure and optimizing the pore structure of the porous carbon material, the specific surface area and conductivity of the layered porous carbon are improved, so that it can improve the rate performance and capacitance characteristics of the electrochemical device during application. At the same time, the presence of a large number of micropores on the surface of the special hierarchical pore structure in the layered porous carbon can improve the storage of ions in the electrochemical device during operation, thereby improving the capacitance characteristics of the electrochemical device, and the presence of mesopores and macropores can alleviate the problem of long-distance transmission of ions in the microporous channel during the operation of the electrochemical device, so that the electrochemical device has a higher rate performance. In addition, the layered porous carbon provided by the present invention is mainly designed for the pore structure and hybrid type of the first porous carbon layer and the second porous carbon layer, and the composition is green and environmentally friendly.

[0184] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A layered porous carbon, characterized in that: The layered porous carbon comprises a first porous carbon layer and a second porous carbon layer located on the surface of the first porous carbon layer; the carbon atoms in the layered porous carbon include sp 3 Carbon atom hybrid bonds and sp 2 Carbon atom hybrid bonds, the pore structure of the hierarchical porous carbon includes micropores, mesopores and macropores; In the first porous carbon layer, the sp 2 Carbon atom hybrid bond content>sp 3 Carbon atom hybrid bond content, the total volume proportion of the mesopores and the macropores>the volume proportion of the micropores; In the second porous carbon layer, the sp 3 Carbon atom hybrid bond content>sp 2 Carbon atom hybrid bond content, the volume proportion of the micropores> the total volume proportion of the mesopores and the macropores.

2. The hierarchical porous carbon according to claim 1, characterized in that In the first porous carbon layer, the sp 3 The carbon atom hybrid bond content and the sp 2 The ratio of carbon atom hybrid bond content is (1-3):(7-9); Preferably, in the first porous carbon layer, the micropore volume accounts for 15-25% of the total pore volume in the first porous carbon layer; Preferably, in the second porous carbon layer, the sp 3 The carbon atom hybrid bond content and the sp 2 The ratio of carbon atom hybrid bond content is (7-9):(1-3); Preferably, in the second porous carbon layer, the micropore volume accounts for 50-60% of the total pore volume in the second porous carbon layer; Preferably, the mass ratio of the first porous carbon layer to the second porous carbon layer is (1-2):(4-6); Preferably, the sp 3 The carbon atom hybrid bond content is higher than the sp 3 Carbon atom hybrid bond content; Preferably, the volume proportion of micropores in the second porous carbon layer is higher than the volume proportion of micropores in the first porous carbon layer; Preferably, the pore size of the micropores in the hierarchical porous carbon is 0.4-1.6 nm; Preferably, the pore size of the mesopores in the hierarchical porous carbon is 2-50 nm; Preferably, the pore size of the macropores in the hierarchical porous carbon is greater than 50 nm; Preferably, the carbon material in the hierarchical porous carbon is amorphous carbon.

3. The layered porous carbon according to claim 1 or 2, characterized in that: The layered porous carbon further includes a doping element located in the second porous carbon layer; Preferably, the doping element includes any one of nitrogen, phosphorus, sulfur or boron, or a combination of at least two thereof; Preferably, the total mass of the layered porous carbon is 100wt%, and the mass percentage of the doping element is 5-20wt%.

4. A method for preparing hierarchical porous carbon according to any one of claims 1 to 3, characterized in that: The preparation method comprises: (1) subjecting a first carbon source to a first carbonization, and then introducing an activated gas to subject a first carbon source to a second carbonization, thereby obtaining a first porous carbon layer; (2) The first porous carbon layer, a second carbon source and a solvent are mixed, dried and then pyrolyzed to form a second porous carbon layer on the surface of the first porous carbon layer to obtain the layered porous carbon.

5. The preparation method according to claim 4, characterized in that: Step (1) The first carbon source includes a biomass carbon source and / or a polymer resin; Preferably, the biomass carbon source includes any one of asphalt, branches, corn cobs or coconut shells; Preferably, the polymer resin includes any one of polyethylene, polypropylene or polyvinyl chloride; Preferably, the temperature of the first carbonization in step (1) is 500-700° C.; Preferably, the first carbonization time in step (1) is 1-20 hours; Preferably, the activation gas in step (1) comprises water vapor and / or carbon dioxide; Preferably, the temperature of the second carbonization in step (1) is 500-700°C; Preferably, the second carbonization time in step (1) is 1-20 hours.

6. The preparation method according to claim 4 or 5, characterized in that: Step (2) the second carbon source comprises an organic carbon source; Preferably, the organic carbon source comprises any one or a combination of at least two of cellulose, polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, glucose, fructose, sucrose, chitosan, lactose, xylitol, thiourea, urea, melamine, p-carboxybenzenesulfonamide or p-nitroaniline; Preferably, in step (2), the mass ratio of the first porous carbon layer to the second carbon source is 1:(1-240); Preferably, in step (2), the mass volume ratio of the first porous carbon layer to the solvent is 1 g:(1-300) mL, preferably 1 g:(50-150) mL; Preferably, the solvent in step (2) comprises any one of water, ethanol, isopropanol or acetone, or a combination of at least two of them.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The mixing temperature in step (2) is 30-80° C. Preferably, the mixing time in step (2) is 0.5-3h; Preferably, the mixing in step (2) is carried out under oil bath conditions.

8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (2), a compound containing a doping element is also added during the mixing process; Preferably, the compound containing the doping element comprises any one or a combination of at least two of a nitrogen-containing compound, a sulfur-containing compound, a phosphorus-containing compound or a boron-containing compound; Preferably, the nitrogen-containing compound comprises any one or a combination of at least two of thiourea, urea, melamine, p-nitroaniline, benzidine, pyrrolidine or 2-naphthylamine; Preferably, the sulfur-containing compound comprises any one or a combination of at least two of p-carboxybenzenesulfonamide, rosiglitazone, 2-thiopheneacetic acid or thiourea; Preferably, the phosphorus-containing compound comprises any one of phosphate, hydrogen phosphate or phospholipid or a combination of at least two thereof; Preferably, the boron-containing compound includes any one of boric acid, tetraboric acid, sodium tetraborate or boron carbide, or a combination of at least two thereof.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The pyrolysis atmosphere in step (2) is any one of nitrogen atmosphere, hydrogen atmosphere or inert gas atmosphere, or a combination of at least two thereof; Preferably, the pyrolysis in step (2) includes a first pyrolysis stage and a second pyrolysis stage; Preferably, the temperature of the first pyrolysis stage is 200-400°C; Preferably, the time of the first pyrolysis stage is 0.5-6h; Preferably, the temperature of the second pyrolysis stage is 500-1000°C; Preferably, the second pyrolysis stage lasts for 8-10 hours.

10. A supercapacitor, characterized in that: The supercapacitor comprises a positive electrode material, wherein the positive electrode material comprises the layered porous carbon according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Composite porous carbon material and preparation method of high-power supercapacitor thereof

    CN108063057A